'Like drinking water after being in the desert’: social-symbolic work of sustainable procurement professionals - Chikwana, Josephine; Alinaghian, Leila; Razmdoost, Kamran (International Purchasing and Supply Education and Research Association (IPSERA), 2025)
This study examines how procurement professionals exercise agency in embedding sustainability within procurement processes, using a social-symbolic work lens. Drawing on 36 interviews and 15 observed meetings, it reveals that sustainable procurement is shaped through practice, legitimacy, and identity work. The findings highlight procurement professionals as change agents, driven by personal values, and challenge the view of procurement as purely operational. The study contributes a framework illustrating how these forms of work interact to drive systemic change, offering both theoretical insights and practical guidance for aligning sustainability with procurement practices and professional roles
Keywords: sustainability; purchasing and supply management; social-symbolic work; social-symbolic object